Profetik Leadership Perspektif Imam As-Suyuti Dalam Tafsir Al-durru Al-mantsur Fi Al-tafsiri Bi Al-Ma’sur - Irkham Auladi; Enjang Burhanudin Yusuf (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2025)
Humans are God's most perfect creation, endowed with reason. Therefore, humans bear the burden of being khalifah fil ardh (vicegerent) on earth. Humans have a role as a leader on earth. To be a good leader, humans must have attitudes as exemplified by the Prophet Muhammad in his personality, known as prophetic leadership. Prophetic attitudes are explained in many verses of the Quran to serve as role models for humans in living their lives. Prophetic leadership is a guide for leaders in government, education, and families. At least four attitudes must be possessed: trustworthiness, sidiq (trustworthiness), tabligh (prophetic conduct), and fathonah (faithfulness). All of these are contained in the Quran. To understand the verses of the Quran, interpretation is necessary. One interesting book of interpretation to discuss is Tafsir Ad-durr Al-mantsur fi al-atfsiri bi Al-Ma'sur, written by Imam Jalaluddin As-Suuyuti. This interpretation interprets verses based on hadith narrations.